2257. Noninfectious Comorbidities Associated With High RDW in HIV-Infected Patients: A Cross-Sectional Study in Miami, Florida. (26th November 2018) - Presser, Javier Baez; Raja, Mohammed; Rugama, Marco Lorio; Milisavljevic, Ana; Zamora, Jose Gonzales
Abstract: Background: Red blood cell distribution width (RDW) is a hematologic parameter that may reflect an underlying inflammatory state. It has been linked to cardiovascular disease, metabolic syndrome and increased mortality in the general population. However, little is known about the comorbidities associated with high RDW in HIV-infected patients. Methods: We conducted a retrospective review of HIV-infected patients treated in the Ryan White Clinic of Jackson Memorial Hospital from January to December 2016. Of the 2, 065 patients who attended our clinic in 2016, a sample of 317 patients was obtained. Our aim was to determine the noninfectious comorbidities associated with high RDW (≥14%) in patients with undetectable HIV viral load. Data were analyzed in SPSS 22, New York, USA. Results: Our study included 317 HIV patients with undetectable HIV viral load, 123 (38.8%) females and 194 (61.2%) males with a mean age of 54.3 (SD ±9.94). Most patients were African American (52.4%) and Hispanic (39.4%). The mean CD4 count was 609.9 cells/μL (SD ±303.48) with a mean CD4/CD8 ratio of 1.04 (SD ±3.8). The mean RDW was 13.6% (SD ± 2.08). High RDW was observed in 94 (29.7%) patients. Hepatitis B and C coinfection were found in 7.6% and 11.4% of patients, respectively. 74 (23.3%) patients reported alcohol use and 103 (32.5%) patients disclosed smoking. Most patients were on antiretroviral therapy (98.4%).The preferred regimen was 2 NRTIs plus an integrase inhibitor (53%). The most frequent noninfectious comorbidities were dyslipidemia (56.8%), hypertension (52.4%), depression (26.8%) and diabetes mellitus (19.6%). In comparison with the rest of the study cohort, the patients with high RDW had a higher proportion of hypertension (61.7% vs. 48.4%, P = 0.031), stroke (7.4% vs. 0.9%, P = 0.001), congestive heart failure (10.6% vs. 2.7%, P = 0.003) and chronic kidney disease (26.6% vs. 10.3%, P < 0.001). They also had significantly lower CD4 count (555.8 vs. 632.7, P = 0.039). No difference was found in myocardial infarction, peripheral vascular disease, dementia, COPD, asthma, cancer, liver disease, dyslipidemia, depression or gastric disease. Conclusion: Hypertension, congestive heart failure, stroke, and chronic kidney disease were conditions associated with high RDW. Our study suggests that high RDW may be a marker of cardiovascular and renal dysfunction in well-controlled HIV-infected patients. Disclosures: All authors: No reported disclosures.